Application of Fused Reality Holographic Image and Navigation Technology in the Puncture Treatment of Hypertensive Intracerebral Hemorrhage - Peng, Chen; Yang, Liu; Yi, Wang; Yidan, Liang; Yanglingxi, Wang; Qingtao, Zhang; Xiaoyong, Tang; Tang, Yongbing; Jia, Wang; Xing, Yu; Zhiqin, Zhu; Yongbing, Deng (Frontiers in Neuroscience, 2022)
Objective Minimally invasive puncture and drainage (MIPD) of hematomas was the preferred option for appropriate patients with hypertensive intracerebral hemorrhage (HICH). The goal of our research was to introduce the MIPD surgery using mixed reality holographic navigation technology (MRHNT). Method We provided the complete workflow for hematoma puncture using MRHNT included three-dimensional model reconstruction by preoperative CT examination, puncture trajectory design, immersive presentation of model, and real environment and hematoma puncture using dual-plane navigation by wearing special equipment. We collected clinical data on eight patients with HICH who underwent MIPD using MRHNT from March 2021 to August 2021, including the hematoma evacuation rate, operation time, deviation in drainage tube target, postoperative complications, and 2-week postoperative GCS. Result The workflow for hematoma puncture using MRHNT were performed in all eight cases, in which the average hematoma evacuation rate was 47.36±9.16%, the average operation time was 82.14±15.74 min, and the average deviation of the drainage tube target was 5.76±0.80 mm. There was no delayed bleeding, acute ischemic stroke, intracranial infection, or epilepsy 2 weeks after surgery. The 2-week postoperative GCS was improved compared with the preoperative GCS. Conclusion The research concluded it was feasible to perform the MIPD by MRHNT on patients with HICH. The risk of general anesthesia and highly professional holographic information processing restricted the promotion of the technology, it was necessary for technical innovation and the accumulation of more case experience and verification of its superiority.